2002
DOI: 10.1042/bj20020154
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of nitric oxide by oxomanganese–salen complexes: a new mechanism for cellular protection by superoxide dismutase/catalase mimetics

Abstract: Manganese-salen complexes (Mn-Salen), including EUK-8 [manganese N,N'-bis(salicylidene)ethylenediamine chloride] and EUK-134 [manganese 3-methoxy N,N'-bis(salicylidene)ethylenediamine chloride], have been reported to possess combined superoxide dismutase (SOD) and catalase mimetic functions. Because of this SOD/catalase mimicry, EUK-8 and EUK-134 have been investigated as possible therapeutic agents in neurological disorders resulting from oxidative stress, including Alzheimer's disease, Parkinson's disease, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 56 publications
(67 reference statements)
5
115
0
1
Order By: Relevance
“…If one does the calculation per molar basis, assuming the MW of the enzyme to be 250,000, and considering its tetramer structure (MW ¼ 62,500), and the MW ¼ 357 for EUK-8, EUK-8 has 7Â10 À5 % of catalase activity (171). In agreement with these calculations, Sharpe et al (284) considered Mn salens to be poor catalysts of H 2 O 2 breakdown (284). Although SOD-like activity is reportedly not dependent on the structure, the structure-activity relationship has been established for catalase-like activity (93,94).…”
Section: B Catalase-like Activity Of Mn Salenssupporting
confidence: 69%
See 1 more Smart Citation
“…If one does the calculation per molar basis, assuming the MW of the enzyme to be 250,000, and considering its tetramer structure (MW ¼ 62,500), and the MW ¼ 357 for EUK-8, EUK-8 has 7Â10 À5 % of catalase activity (171). In agreement with these calculations, Sharpe et al (284) considered Mn salens to be poor catalysts of H 2 O 2 breakdown (284). Although SOD-like activity is reportedly not dependent on the structure, the structure-activity relationship has been established for catalase-like activity (93,94).…”
Section: B Catalase-like Activity Of Mn Salenssupporting
confidence: 69%
“…Besides O 2 ·À -and H 2 O 2 -related activity, Sharpe et al (284) reported the reactivity of EUK-8 and EUK-134 toward OCl À and ONOO À , in which Mn(V) oxo species were formed by a two-electron process, thus giving rise to the benign species, H 2 O, O 2 , and NO 2 ·À . The Mn(V) oxo species can react with · NO, giving rise to · NO 2 , which will combine with · NO, giving rise to N 2 O 3 , which, with water, will produce HNO 2 .…”
Section: Reactivity Toward Other Ros=rnsmentioning
confidence: 99%
“…Furthermore, SOD can have pro-oxidant activities at higher concentrations, e.g., Cu/ZnSOD can promote the generation of hydroxyl radicals [16] and [48] and inhibit the ability of superoxide to regulate lipid peroxidation [19] and [49]. This has generated much interest in SODm, leading to the development of agents including macrocyclics, manganese salens, nitroxides, porphyrins, and many other catalytic antioxidants [15], [20], [50], [51], [52], [53], [54] and [55]. However, many of these have also suffered problems ranging from cytotoxicity to poor stability [23] and [56].…”
Section: Discussionmentioning
confidence: 99%
“…N (G)-monomethyl-L-arginine (NMA) (a reversible inhibitor of NO synthase) prevented the dysfunction or destruction of cultured islets and markedly decreased the time needed to restore euglycemia after intraportal transplantation of islets in diabetic rats [64] . Direct antioxidants such as vitamin E and salen-manganese compounds can prevent NO and nitrite radicals as well as ROS [65,66] thus may play a protective role.…”
Section: Discussionmentioning
confidence: 99%